A pilot prospective study based on scanning OCT: the intraoperative vault model predicts postoperative vault - Zhongjun Tang; Yanze Yu; Jing Zhao; Yang Shen; Shengtao Liu; Xingtao Zhou (BMC Ophthalmology)
Abstract Purpose To evaluate the correlation between intraoperative vault measured by optical coherence tomography (OCT) and postoperative vault, and to assess dynamic changes in vault following EVO implantable collamer lens (ICL) implantation. Setting Eye and ENT Hospital of Fudan University. Design Prospective observational study. Methods This prospective study enrolled 14 patients (5 males, 9 females) who underwent EVO ICL implantation at the Eye and ENT Hospital of Fudan University between July and August 2024, involving a total of 27 eyes. The mean age of the patients was 25.5 ± 4.4 years (range: 19 to35 years), and the average manifest refraction spherical equivalent was − 7.84 ± 2.25 D (range: −11.63 to − 2.00 D). Intraoperative OCT was used to measure real-time vault height without the application of viscoelastic agents. Central vault was measured using CASIA-2 immediately after ICL implantation and reassessed at 1 day, 1 week, and 1 month postoperatively. At each follow-up, visual acuity, subjective and objective refraction, and anterior segment parameters were recorded. Results The mean intraoperative vault was 937.30 ± 402.27 μm. Postoperative vault measurements demonstrated a progressive decline: 912.00 ± 269.96 μm at 2 hours, 777.43 ± 252.19 μm at 1 day, 722.22 ± 226.37 μm at 1 week, and 675.98 ± 224.34 μm at 1 month. A strong correlation was observed between intraoperative and postoperative vault values, with an r² of 0.827 at 2 hours. Bland–Altman analysis indicated a systematic bias of 39.63 μm, with 92.6% of eyes falling within the 95% limits of agreement. The anterior chamber depth to both the crystalline lens and ICL remained stable throughout the postoperative period. Conclusion The vault measured by intraoperative OCT during EVO ICL implantation closely corresponded with postoperative measurements obtained via CASIA-2, and vault decreased in the early postoperative period.